Multicentre, single-blind randomised controlled trial comparing MyndMove neuromodulation therapy with conventional therapy in traumatic spinal cord injury: a protocol study - Lehana Thabane; Milos R Popovic; Kristin E Musselman; Daria O'Reilly; James M Bowen; Kim D Anderson; James R Wilson; Radha Korupolu; Jacqueline Pierce; Naaz Kapadia (BMJ Open)
Introduction This protocol is describing a multicentre, single-blind randomised controlled trial. The objective is to compare the efficacy of MyndMove therapy versus conventional therapy (CT) in improving upper extremity function in individuals with C4–C7 traumatic, incomplete spinal cord injury (SCI). It is being conducted in two US and two Canadian SCI rehabilitation centres.Methods and analysis Sixty people aged 18 years or older with a C4–C7 incomplete (AIS B-D) SCI between 4 months and 8 years postinjury are randomised to receive 40 sessions of MyndMove neuromodulation therapy or CT within a 14-week period of time. Therapy sessions are 1 hour in duration with a dose of 3–5 sessions per week. Assessments occur prior to randomisation, after 20 sessions, after 40 sessions and 10 weeks after the last session. The primary outcome measure is the efficacy of MyndMove therapy versus CT in improving upper extremity function as measured by Spinal Cord Independence Measure III: Self-Care subscore after 40 sessions. Secondary outcomes include: (1) improvements in the SCIM mobility subscore; (2) upper limb functions measured by Graded Redefined Assessment of Strength, Sensibility and Prehension and (3) Toronto Rehab Institute Hand Function Test; (4) To assess safety as measured by serious and non-serious adverse events recorded for participants in both groups of the study population over the duration of the study; (5) to compare the change in quality of life as measured by the Spinal Cord Injury-Quality of Life; and (6) to evaluate the impact on healthcare resource utilisation.Ethics and dissemination All ethical approvals were obtained prior to enrolling any participants. Dissemination of the results of the study will be made at peer-reviewed academic meetings and through peer-reviewed medical journalsTrial registration number NCT03439319